Application of Vee Diagram in Reconstructing Laboratory Activity Design on Diffusion-Osmosis Concept - Ahmad Soleh; Widi Purwianingsih; Kusnadi; Bambang Supriatno; Amprasto (Quagga: Jurnal Pendidikan dan Biologi, 2025)
Implementing the Merdeka curriculum is a record of Indonesia's long journey of education dynamics. One of the reforms visible from implementing the Merdeka curriculum is the existence of science process skills (KPS), as stated in the learning outcomes, especially in the skills element. Diffusion and osmosis are materials that are consistently included in the curriculum. As one part of science learning, diffusion-osmosis cannot escape the practicum learning method that involves science process skills and needs to contain aspects of Vee Diagram knowledge construction. The ideal Laboratory Activity Design (DKL) as a support for diffusion-osmosis practicum activities is still minimal, especially since the implementation of the Merdeka curriculum is still relatively new. Through the descriptive qualitative research method with an analysis-try-reconstruction (ANCOR) approach, this research aims to analyze the quality of diffusion-osmosis student worksheets (DKL) in high school textbooks and then test and reconstruct the DKL. The analysis and pilot test findings showed that DKL was unsuitable for knowledge construction. The results of DKL reconstruction use aspects of the Vee Diagram and Science Process Skills (KPS) to align with the expected competency achievements in implementing the Merdeka Curriculum.